2016
DOI: 10.1097/sap.0000000000000723
|View full text |Cite
|
Sign up to set email alerts
|

Superior Gluteal Artery Perforator Flap

Abstract: Although utilization of buttock tissue for breast reconstruction can be challenging and requires microsurgical expertise, in the hands of experienced microsurgeons the SGAP flap is a safe and reliable option for autologous breast reconstruction with minimal donor-site morbidity and excellent aesthetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…For decades, surgical debridement with subsequent reconstruction was the best treatment for these patients, and different kinds of surgical methods were designed for this purpose. Since Koshima et al first described a gluteal artery perforator-based flap for the reconstruction of sacral pressure sores, many methods based on superior gluteal artery, inferior gluteal artery and parasacral artery perforators have been utilised widely in many aspects of plastic surgery due to their advantages (3,5,8,9). Among these, the SGAP flap has been used the most because it provides many advantages related to safety and reliability, less blood loss, preservation of muscles, less donor-site morbidity and suitability for even extensive defects (5,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…For decades, surgical debridement with subsequent reconstruction was the best treatment for these patients, and different kinds of surgical methods were designed for this purpose. Since Koshima et al first described a gluteal artery perforator-based flap for the reconstruction of sacral pressure sores, many methods based on superior gluteal artery, inferior gluteal artery and parasacral artery perforators have been utilised widely in many aspects of plastic surgery due to their advantages (3,5,8,9). Among these, the SGAP flap has been used the most because it provides many advantages related to safety and reliability, less blood loss, preservation of muscles, less donor-site morbidity and suitability for even extensive defects (5,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] With the revolutionary changes in microsurgery, the spectrum of free flap extended into the new territory of perforator-based flaps. [12][13][14][15][16] Cavadas et al in 2001 1 in their landmark study found out multiple perforating vessels coming out from gastrocnemius muscle supplying the skin in a fixed pattern. They correlated it with clinical cases and successfully performed MSAP free flap.…”
Section: Discussionmentioning
confidence: 99%
“…The first superior gluteal artery myocutaneous flap for breast reconstruction was by Fujino in 1975 [38]. With the development of perforator flaps, Allen in 1993 developed the superior gluteal artery perforator (SGAP) flap to allow for a longer vascular pedicle and gluteus maximus muscle preservation [39,40]. The use of the SGAP is not considered the first option for breast reconstruction because of a tedious flap dissection, change in positioning in the operating room, smaller volume flap, and gluteal scarring [40].…”
Section: Superior Gluteal Artery Perforator (Sgap)mentioning
confidence: 99%
“…The height of the flap can vary from 7 to 14 cm but must be confirmed with the pinch test to allow for appropriate closure (Figure 21). The length of the flap can also vary from 18 to 30 cm [30,40]. Immediate Breast Reconstruction with Free Autologous Tissue Transfer DOI: http://dx.doi.org/10.5772/intechopen.85652…”
Section: Markingmentioning
confidence: 99%
See 1 more Smart Citation